2020
DOI: 10.3390/cells9112418
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory Role of AQP4 in Mice Subjected to Intrastriatal Injections of the Parkinsonogenic Toxin MPP+

Abstract: Aquaporin-4 (AQP4) is critically involved in brain water and volume homeostasis and has been implicated in a wide range of pathological conditions. Notably, evidence has been accrued to suggest that AQP4 plays a proinflammatory role by promoting release of astrocytic cytokines that activate microglia and other astrocytes. Neuroinflammation is a hallmark of Parkinson’s disease (PD), and we have previously shown that astrocytes in substantia nigra (SN) are enriched in AQP4 relative to cortical astrocytes, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…Also, the study concluded that the reason for these opposing findings lay in the integrity or otherwise of the BBB in mice. In contrast to the intact BBB in this study, disruption of the BBB can expose neurons and glial cells directly to inflammatory cells and factors ( Prydz et al, 2020 ). The swelling effect in AQP4-induced astrocytes appeared to also be observed in the brain tissue of patients with PD, who show more severe water accumulation in the substantia nigra.…”
Section: Astrocytic Ion Channels In Parkinson’s Diseasementioning
confidence: 84%
See 1 more Smart Citation
“…Also, the study concluded that the reason for these opposing findings lay in the integrity or otherwise of the BBB in mice. In contrast to the intact BBB in this study, disruption of the BBB can expose neurons and glial cells directly to inflammatory cells and factors ( Prydz et al, 2020 ). The swelling effect in AQP4-induced astrocytes appeared to also be observed in the brain tissue of patients with PD, who show more severe water accumulation in the substantia nigra.…”
Section: Astrocytic Ion Channels In Parkinson’s Diseasementioning
confidence: 84%
“…However, evidence exists that AQP4-mediated astrocyte swelling also has a role in promoting neuroinflammation. Prydz et al (2020) also injected MPP + into the striatum of AQP4-deficient mice. Wild-type mice were found to have more pronounced neuroinflammation than AQP4-KO mice and a deficiency of astrocytic AQP4 channels induced weaker microglia activation than in wild-type mice.…”
Section: Astrocytic Ion Channels In Parkinson’s Diseasementioning
confidence: 99%
“…Additionally, a model of CCI for post-traumatic epilepsy also indicated that dysregulation of AQP4 leads to neurological deficits, which can be through the swelling of astrocytic endfeet (Szu et al, 2020;Lu et al, 2021). Theories have also found dysregulation of AQP4 to play a pro-inflammatory role contributing to neurological deficits in diseases such as Parkinson's; thus, the role of AQP4 following closed-head impact TBI is important to study (Tamtaji et al, 2019;Prydz et al, 2020). While the experimental design of the compared studies may differ, the similarities in results, with both the present and a compared study showing increases in AQP4 following injury and disease, suggests that the closed-head aspect of this model still produces pathology that is representative of pathology reported in traditional CCI models that replicate pathology observed following mTBI in humans (Yao et al, 2015;Szu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that deletion of aquaporin-4 (AQP4), the predominant aquaporin in the central nervous system and a water-selective member of the aquaporin family, significantly reduces the inflammatory response to intrastriatal injections of 1-methyl-4-phenylpyridinium (MPP + )—a parkinsonogenic compound that is known to induce a strong inflammatory response [ 9 ]. This finding inspired us to use the same experimental model to explore whether AQP9—similar to AQP4 and analogous to the situation in peripheral tissues—plays a proinflammatory role in the brain.…”
Section: Introductionmentioning
confidence: 99%